2014
DOI: 10.1016/j.socscimed.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The pathways from perceived discrimination to self-rated health: An investigation of the roles of distrust, social capital, and health behaviors

Abstract: Although there has been extensive research on the adverse impacts of perceived discrimination on health, it remains unclear how perceived discrimination gets under the skin. This paper develops a comprehensive structural equation model (SEM) by incorporating both the direct effects of perceived discrimination on self-rated health (SRH), a powerful predictor for many health outcomes, and the indirect effects of perceived discrimination on SRH through health care system distrust, neighborhood social capital, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 60 publications
11
86
0
3
Order By: Relevance
“…Unrelated to abstinence were measures of income, employment status, housing stability, nicotine dependence, mental health, and racial discrimination. Prior studies have supported the link between discrimination experiences, nicotine dependence and heavier smoking, [56][57][58] and Kendzor and colleagues 59 found a greater number of racial discrimination experiences predicted lower tobacco abstinence among treatment seeking Latinos; however, Fagerström Test of Cigarette Dependence and cigarettes per day were not associated with discrimination in our sample.…”
Section: Discussionsupporting
confidence: 52%
“…Unrelated to abstinence were measures of income, employment status, housing stability, nicotine dependence, mental health, and racial discrimination. Prior studies have supported the link between discrimination experiences, nicotine dependence and heavier smoking, [56][57][58] and Kendzor and colleagues 59 found a greater number of racial discrimination experiences predicted lower tobacco abstinence among treatment seeking Latinos; however, Fagerström Test of Cigarette Dependence and cigarettes per day were not associated with discrimination in our sample.…”
Section: Discussionsupporting
confidence: 52%
“…Example investigations include discrimination and social resistance [78, 79], emotions and stress [80, 81], and cognitive processes such as decision-making and framing [82]. Attempts to incorporate feedback processes conceptually and methodologically are growing [83, 84], as are efforts to address the challenges of causality [85].…”
Section: Biosocial Processes: Situating Individuals In Social and mentioning
confidence: 99%
“…Ethnicity-discrimination and ethnicity-SOC interaction terms were included to assess moderation. All models controlled for demographic variables mentioned above and all regression procedures were performed using the PROCESS macro in SPSS (11).…”
Section: Discussionmentioning
confidence: 99%
“…The strongest and most consistent findings show a negative association between perceived discrimination and mental health and self-rated health in oppressed racial groups [1][2][3][4][5]. Discrimination is suggested to be a stressor among individuals that experience discrimination [6] and this may increase use of addictive substances [7][8][9], may influence risk behaviors, prevent lifestyle changes and increase prevalence of hypertension [10][11][12]. Furthermore, in a study measuring the length of telomeres (repetitive DNA sequences that protect the end of the chromosome and shorten with every replication, the shorter they are the shorter life expectancy is), it was demonstrated that those reporting higher rates of discrimination had shorter telomeres suggesting discrimination may affect health by accelerating biological aging [13].…”
Section: Introductionmentioning
confidence: 99%